It's time to reconsider how we define health: Perspective from disability and chronic condition. Issue 4 (October 2021) - Krahn, Gloria L.; Robinson, Ann; Murray, Alexa J.; Havercamp, Susan M.; ,; Havercamp, Susan; Andridge, Rebecca; Arnold, L. Eugene; Barnhill, Jarrett; Bodle, Shawn; Boerner, Ethan; Bonardi, Alixe; et al.
Abstract: Our understanding of health has changed substantially since the World Health Organization initially defined health in 1948 as "a state of complete physical, mental and social and well-being and not merely the absence of disease or infirmity". These changes include reconceptualizing health on a continuum rather than as a static state, and adding existential health to physical, mental, and social well-being. Further, good health requires adaptation in coping with stress and is influenced by social, personal and environmental factors. Building on prior work, we propose a reconsidered 2020 definition: "Health is the dynamic balance of physical, mental, social, and existential well-being in adapting to conditions of life and the environment." Health is dynamic, continuous, multidimensional, distinct from function, and determined by balance and adaptation. This new definition has implications for research, policies, and practice, with particular relevance for health considered within a context of disability and chronic conditions.